2019
DOI: 10.33108/visnyk_tntu2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of characteristic of powder wire with the CuO / AL exothermic mixture

Abstract: The paper the results of research is presented and the level of influence of the parameters of surfacing and the amount of exothermic mixture in the composition of self-shielding flux-cored wire on the deposition rate factor and spattering factor are analyzed. The analysis of the experiment was performed using the Taguchi method, in addition, to determine the influence of individual factors on the studied parameters (ad, ψS), analysis of variance (ANOVA) is fulfilled. It was found that for the deposition rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Weld deposition were realized as three-layered to minimize impact of mixing the layer with base material. Welding parameters where chosen to provide high deposition values (high deposition rate and low spattering factor) [16], as well as for low solution of the deposited metal with the base metal and providing welded bead optimal shape [17]. Thus, hardfacing was performed by FCAW-S were as follows: wire feed speed WFS=1.85 m/min, arc welding voltage Ua =28 V, travel speed TS=0.3 m/min, contact tip to work distance CTWD=45 mm, DCRP Polarity, temperature preheating Tp=250…300 °C.…”
Section: Hardfacing Technologymentioning
confidence: 99%
“…Weld deposition were realized as three-layered to minimize impact of mixing the layer with base material. Welding parameters where chosen to provide high deposition values (high deposition rate and low spattering factor) [16], as well as for low solution of the deposited metal with the base metal and providing welded bead optimal shape [17]. Thus, hardfacing was performed by FCAW-S were as follows: wire feed speed WFS=1.85 m/min, arc welding voltage Ua =28 V, travel speed TS=0.3 m/min, contact tip to work distance CTWD=45 mm, DCRP Polarity, temperature preheating Tp=250…300 °C.…”
Section: Hardfacing Technologymentioning
confidence: 99%
“…Improving productivity and energy efficiency is one of the main challenges for developers of welding and surfacing filler materials. One of the promising methods for increasing energy efficiency (reducing energy consumption) and increasing the productivity of FCAW-S is the introduction of an exothermic addition into the core filler of a flux-cored wire electrode [45][46][47][48][49]. Recent studies of the author have shown the effectiveness of the desired copper content provision due to introduction of exothermic addition CuO -Al [48,50].…”
Section: Researchmentioning
confidence: 99%
“…Weld deposition were realized as three-layered to minimize impact of mixing the layer with base material. Welding parameters where chosen to provide high deposition values (high deposition rate and low spattering factor) [45,47], as well as for low solution of the deposited metal with the base metal and providing welded bead optimal shape [48,49]. Thus, hardfacing was performed by FCAW-S according to the parameters are shown in Table 3.…”
Section: Hardfacing Processmentioning
confidence: 99%